The Unheard Threat: Scientific Mapping of Studies Investigating the Impact of Operating Room Noise on Patient Outcomes - Gülşen, Muaz; Özsoy, Hatice; Çankaya, Askeri (Lippincott Williams and Wilkins, 2026)
Background: – Surgical outcomes depend not only on clinical expertise but also on environmental factors, among which operating room noise is an important yet often underestimated risk factor. Rather than providing an extensive background, this study focuses on mapping how operating room noise and patient outcomes have been conceptualized in the scientific literature using bibliometric scientific mapping methods to identify intellectual structures, thematic trends, and research gaps. Method: – This retrospective descriptive study analyzed 54 original research articles identified through a predefined and structured bibliometric search of the Web of Science Core Collection conducted on April 25, 2025. Search terms included combinations of “operating room, ” “noise, ” and “patient.” Bibliometric analyses were performed using VOSviewer and the Bibliometrix R package, examining publication trends, citation patterns, keyword co-occurrences, and collaboration networks. Results: – The earliest publication was identified in 1986, with 41.51% of articles published in the last 5 years and a marked increase after 2020. The analyzed studies were published in 43 journals and authored by 247 researchers, with a mean of 4.74 authors and 18.72 citations per article. The United States was the most productive and most cited country. Core themes centered on “noise, ” “patient safety, ” and “communication, ” while recent trends highlighted “auditory alarms, ” “staff stress, ” and “surgeon workload.” Author productivity followed Lotka law, and institutional contributions were concentrated in Vanderbilt University and the University of Neuchâtel. Conclusion: – The findings demonstrate increasing academic attention to operating room noise and its relationship with patient outcomes; however, the literature remains fragmented, predominantly observational, and largely single-centered. This bibliometric mapping highlights the need for multicenter, experimental, and interdisciplinary research designs, as well as clearer outcome definitions, to better capture the clinical, psychosocial, and organizational pathways through which operating room noise may influence patient safety and perioperative care quality. Copyright © 2026 Wolters Kluwer Health, Inc. All rights reserved.
Keywords: bibliometric analysis; Bibliometrix; noise; operating room noise; patient outcomes; VOSviewer